Hubungan Media Pembelajaran Guru Terhadap Motivasi Belajar Siswa pada Pembelajaran PAI di Kelas VIII SMP Al Hidayah Medan Tembung - Dinda Zulaikha; Arlina Arlina (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Learning media are an essential strategy in modern education due to their role in enhancing student engagement and learning motivation, including in Islamic Religious Education (IRE). Numerous studies indicate that the use of audiovisual and interactive media can increase students’ learning motivation. However, in practice, IRE instruction in several junior high schools is still dominated by printed materials and lecture-based methods, which contributes to low student motivation. This condition was also found at SMP Al Hidayah Medan Tembung and is influenced by limited facilities and inadequate technological skills among some teachers. This study aims to examine the relationship between teachers’ use of learning media and students’ learning motivation in IRE for eighth-grade students at SMP Al Hidayah Medan Tembung. The research employed a quantitative approach with a correlational design. Data were collected using Likert-scale questionnaires measuring learning media as the independent variable and students’ learning motivation as the dependent variable. The research instruments were tested for validity and reliability, while data analysis was conducted using SPSS through Pearson correlation and simple linear regression tests. The results indicate a positive and significant relationship between teachers’ use of learning media and students’ motivation in IRE learning. The more varied and effective the learning media used, the higher the students’ learning motivation. These findings emphasize the importance of learning media as a supporting factor in enhancing students’ motivation in Islamic Religious Education at the junior high school level.